Social Learning E-Module for Optimizing Critical Thinking Skills - Karyadi Hidayat; Sapriya; Said Hamid Hasan; Erlina Wiyanarti (Universitas Pendidikan Ganesha, 2023)
Digitalization of learning is appropriate as a form of adjustment in facing the challenges of the 21st century. The problem faced is that teaching materials that are on the characteristics of students need to be developed properly, especially digital teaching materials, which also support improving critical thinking skills as one of the 21st-century skills. This study aims to develop digital teaching materials (e-modules) in social science learning to optimize students' critical thinking skills. The research design refers to Rowntree's development research which includes planning, development and evaluation. The e-module effectiveness test was carried out using a one-group pretest-posttest design. The research subjects were 104 class VIII students. Data was collected through interviews, observation, questionnaires and essay tests. Data analysis used the paired samples test, with the prerequisite test data being normally distributed and homogeneous. The tests' results stated that the research data were normally distributed and homogeneous. The results of the paired samples test stated that the social science learning e-module had a positive and significant contribution. It was concluded that social science learning e-modules were effectively used to optimize students' critical thinking skills.